Contextualizing the Raden Intan II Commemoration Tradition in South Lampung as a Source for Character-Based History Education - Winda Pitriani Parhamah; Aman Aman; Sumargono Sumargono; Febriana Khoiriyah; Hadi Waluyo; Nadira Febri Faradila (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
Character degradation has become a trend as a consequence of massive globalization. The deconstruction of a curriculum oriented towards character building can be achieved by integrating local traditions as a source of contextual learning. This study aims to explore history, analyze character values in the Haul Raden Intan II tradition, and apply them in history lessons. A qualitative case study approach was used to explore the phenomenon of the Haul Raden Intan II tradition in South Lampung. Data collection was carried out through in-depth interviews with three key informants, namely the family of the heir and traditional leaders, religious leaders, and students who are cultural activists, supported by direct observation and documentation. Secondary sources, including scientific articles and supporting books, were used as references. Data analysis used interactive techniques by Miles and Huberman. The research findings show that the haul tradition has become the cultural identity of the people of South Lampung, serving to preserve the exemplary character of Raden Intan II. The Raden Intan II haul tradition's procession embodies values aligned with the Graduate Profile Dimensions, namely faith and devotion to God Almighty, citizenship, collaboration, critical thinking, and independence. The integration of the character values of the Raden Intan II haul tradition into history learning is presented in the material on the Struggle of the Local People Against the Colonizers, which uses a historical inquiry model based on mini-research and edu-vlogs, culminating in an authentic assessment.